Analisis Representasi dan Cultural Universal Komunitas Etnis Tionghoa dalam Film Apanya Dong (1983) - Satria Adhitama (CV. ITTC INDONESIA, 2025)
Film as a popular cultural medium has an important role in representing ethnic identity and social reality. The problem studied in this study is how the Chinese community is represented in the film Apanya Dong (1983) by Nya' Abbas Akup which was produced during the New Order period, when Chinese cultural expression was limited by state policies. The purpose of this research is to understand how the film presents Chinese ethnic identity in the midst of assimilation pressure. The research uses a qualitative method with a film study approach as a social discourse. The analysis was carried out through Stuart Hall's theory of representation and the concept of cultural universality from Kluckhohn and Kroeber, by examining the narrative aspects, characters, and cultural elements displayed. The results of the study show that the film Apanya Dong showcases the Chinese community through characters such as Babah Ho Liang, Pei Pei, and Ti Lian Nio, as well as raising cultural elements in the form of belief systems, social structures, traditional clothing, language, and arts such as barongsai, erhu, and xylophone kromong. Although the portrayal is often packed in comedy and stereotypes, the characters are still shown to have agency. Thus, this film serves as a cultural mirror as well as a means of subtle resistance, which emphasizes that film can be an inclusive medium of representation and strengthen understanding of Indonesia's cultural diversity.